Insights Into the Regulation of Gynecological Inflammation-Mediated Malignancy by Metalloproteinases - Begum, Yasmin; Pandit, Anuradha; Swarnakar, Snehasikta (Frontiers in Cell and Developmental Biology, 2021)
Gynecological illness accounts for around 4.5 % of the global disease burden, which is higher than other key global health concerns such as malaria (1.04 %), TB (1.9 %), ischemic heart disease (2.2 %), and maternal disorders (3.5 %). Gynecological conditions in women of reproductive age are linked to both in terms of diagnosis and treatment, especially in low-income economies, which poses a serious social problem. A greater understanding of health promotion and illness management can help to prevent diseases in gynecology. Due to the lack of established biomarkers, the identification of gynecological diseases, including malignancies, has proven to be challenging in most situations, and histological exams remain the gold standard. Metalloproteases (MMPs, ADAMs, ADAMTSs) and their endogenous inhibitors (TIMPs) modulate the protease-dependent bioavailability of local niche components (e.g. growth factors), matrix turnover, and cellular interactions to govern specific physical and biochemical characteristics of the environment. Matrix metalloproteinases (MMPs), A Disintegrin and Metalloproteinase (ADAM), and A Disintegrin and Metalloproteinase with Thrombospondin Motif (ADAMTS) are zinc-dependent endopeptidases that contribute significantly to the disintegration of extracellular matrix proteins and shedding of membrane-bound receptor molecules in several diseases, including arthritis. MMPs are noteworthy genes associated with cancer development, functional angiogenesis, invasion, metastasis, and immune surveillance evasion. These genes are often elevated in cancer and multiple benign gynecological disorders like endometriosis, according to research. Migration through the extracellular matrix, which involves proteolytic activity, is an essential step in tumor cell extravasation and metastasis. However, none of the MMPs' expression patterns, as well as their diagnostic and prognostic potential, have been studied in a pan-cancer context. The latter plays a very important role in cell signaling and might be used as a cancer treatment target. ADAMs are implicated in tumor cell proliferation, angiogenesis, and metastasis. Therefore, strategies targeting MMPs, ADAMs/ADAMTS may constitute an important target for the design of cancer drugs. This review will focus on the contribution of the aforementioned metalloproteases in regulating gynecological disorders and their subsequent manipulation for therapeutic intervention.